Environmentally friendly refrigeration with thermoacoustic - Mohd. Ghazali, Normah (Universiti Teknologi Malaysia, 2006)
Use of CFC-contained systems has caused severe environmental hazards that have researchers looking for alternatives. Previous studies have shown that thermoacoustic technology is suited a candidate for conventional vapor compression cooling system in particular for special uses. In this research, theoretical, numerical and experimental studies were completed to identify optimum operating conditions for the design, fabrication, and operation of a thermoacoustic refrigerator. The system uses no refrigerant or compressor, and the only mechanical moving part is the loudspeaker connected to a signal generator that produces the acoustics. Numerical simulation found that mixtures of Helium and other noble gases do produce greater thermoacoustic effects as reported theoretically and experimentally. A series of tests both in the laboratory and at selected sites with a system fabricated under Vot 71891 (Padang Kawad UTM, Rumah Alumni UTM, and outside tutorial room) found that the thermoacoustic effects were consistent and reliable. The system fabricated with this grant is made of copper and aluminium with a sinusoidal section to reduce power loss and can operate up to a maximum of 10 bar. The system can be taken apart if different stack geometry or material is to be studied.